INVESTIGATION OF CANNY TECHNIQUE FOR EDGE DETECTION IN IMAGE PROCESSING - Liew, Hui Fien (Universiti Malaysia Sarawak, (UNIMAS), 2004)
Edge detection is an important task in image processing. It is an essential preliminary step in most automatic pictorial pattern recognition and scene analysis problems. The aim of this project is to investigate the Canny technique for edge detection in detail. Then, a comparison of various methods for edge detection is made. These methods include Roberts, Prewitt, Sobel, Frei-Chen, Scharr, Kirsch, Robinson and Canny. Firstly, the mechanisms of edge detectors are discussed. Then, their algorithms are implemented in MATLAB. A significant difference in the performance of edge detectors is determined and discussed. Canny presents the best performance among all the edge detectors. However, one problem with the basic Canny technique is that of so-called `Y junctions'.